The impact of legislation on the internal audit function - Jones, K.; Baskerville, Richard; Sriram, R.; Ramesh, B. (2017)
© Emerald Publishing Limited. Purpose - The purpose of this study is to show how the presence of change caused a shift in the roles and responsibilities of the internal audit function (IAF). Design/methodology/approach - The methodological design/approach was constructed by combining specific aspects of widely known management accounting and organizational change frameworks. The theoretical premise was based on the old institutional economics component of institutional theory. As such, this study used the case study method to examine and analyze the impact of this change in eight specific organizations using the new two-tiered organizational change framework. Findings - This new framework analyzes the multidimensional facets of organizational change in the IAF. From the findings, it was observed that the change can be evolutionary, episodic, continuous and/or teleological, and people, organisms and organizations that are subject to it will react or respond to that change in a myriad of ways. Practical implications - Moreover, the implications of change can be environmental, socioeconomic and political. Originality/value - This study makes an intellectual contribution by introducing a new two-tiered organizational change framework to explain the IAF's response to the environmental change factor of regulation.